THE EFFECT OF UREA SUPLEMENTATION IN MATURATION MEDIA OF BOVINE OOCYTE IN VITRO TOWARDS EXPRESSION OF BAX, BCL-2 AND BAX/BCL-2 RATIO - Kartikasari, Dhesy; Mulyati, Sri; Utama, Suzanita; srianto, Pudji; Widjiati, Widjiati; Plumeriastuti, Hani (Universitas Syiah Kuala, 2020)
This study aims to evaluate the expression of BAX, BCL-2, and BAX/BCL-2 ratio in maturation media of cow oocytes which supplemented with Urea in vitro because BAX and BCL-2 are the main regulators of apoptosis.A total of 263 oocytes from follicle aspirations originating from ovaries taken from slaughterhouses and were saturated with 3 addition of urea which was divided into three groups. The control group (P0) was control group without the addition of urea, P1 group was added with urea 20 mg/dL, while P2 group was added with urea 40 mg/dL.The results of in vitro oocyte maturation were continued with identification using immunocytochemical staining with the addition of BAX and BCL-2 antibodies.Positive results showed a brownish color on the oocyte and its cumulus.The results of this study indicated that there were significant differences (P0.05) in BAX and BCL-2 expression, although both curves were equally increase. The increase in BCL-2 was more significant than BAX, while the BAX BCL-2 ratio did not show a significant difference (P0.05) in whichthe curve of BAX/BCL-2 ratio was decreased.It can be concluded that the addition of urea does not affect the level of apoptosis.